A View of Death Narrative of Pre-war Malayan Chinese Novels (战前马华小说中死亡叙事模式图景) - OOI (é»„æ·‘è´ž), Soh Chen; CHING (éƒ‘åºæ²³), Thing Ho (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2018)
Abstract The pre-war overseas Chinese in Malaya were in a stormy historical social environment. Death brought them direct impact no matter it is regarding the death of others or they themselves face the threats. For the thought of death and life stayed along with them through the difficult years, the death and dying narrative became an important proposition of their on-site experience in Malaya during pre-war. Inspired by this, this article attempts to summarize, analyse and sort out the types of death narrative modes in pre-war Malayan Chinese novels by referring to the background of Malayan Chinese social history. For the type of death narrative modes, this paper agrees with Wang Xiaohuan’s point of view, and at the same time it meets the real situation of the death narrative text of Pre-war Mahua Literature. Therefore, the types of Pre-war Mahua death narrative modes are divided into three categories, namely, physical death, mental death and introspection of life. 摘要 战前南来华人处在风雨飘摇的历史社会环境下，无论是旁观他人的死亡或是自己面临死亡的威胁，死亡带给他们的是直接的冲击。死亡与生命的思考和念想伴随着他们走过那段艰难的岁月，死亡叙事自然成了战前在地经验的重要命题。本文即是在这样的启发下，企图透过在战前马华社会历史背景的映衬下，细致地归纳、分析和梳理战前马华小说中的死亡叙事模式的类型。对于死亡叙事模式类型，本文认同王小环的观点，同时认为其符合战前马华文学死亡叙事文本的真实情况，因此将战前马华死亡叙事模式类型分为三类，即身体死亡、精神死亡以及生命自省。